Stage-specific embryonic antigen-3 (SSEA-3) and β3GalT5 are cancer specific and significant markers for breast cancer stem cells - Cheung, Sarah K. C.; Chuang, Po-Kai; Huang, Han-Wen; Hwang-Verslues, Wendy W.; Cho, Candy Hsin-Hua; Yang, Wen-Bin; Shen, Chia-Ning; Hsiao, Michael; Hsu, Tsui-Ling; Chang, Chuan-Fa; Wong, Chi-Huey (Proceedings of the National Academy of Sciences - PNAS, 2016)
The discovery of cancer stem cells (CSCs), which are responsible for self-renewal and tumor growth in heterogeneous cancer tissues, has stimulated interests in developing new cancer therapies and early diagnosis. However, the markers currently used for isolation of CSCs are often not selective enough to enrich CSCs for the study of this special cell population. Here we show that the breast CSCs isolated with CD44⁺CD24-/loSSEA-3⁺ or ESAhiPROCRhiSSEA-3⁺ markers had higher tumorigenicity than those with conventional markers in vitro and in vivo. As few as 10 cells with CD44⁺CD24-/loSSEA-3⁺ formed tumor in mice, compared with more than 100 cells with CD44⁺CD24-/lo. Suppression of SSEA-3 expression by knockdown of the gene encoding β-1,3-galactosyltransferase 5 (β3GalT5) in the globo-series pathway, led to apoptosis in cancer cells specifically but had no effect on normal cells. This finding is further supported by the analysis of SSEA-3 and the two related globo-series epitopes SSEA4 and globo-H in stem cells (embryonic stem cells and induced pluripotent stem cells) and various normal and cancer cells, and by the antibody approach to target the globo-series glycans and the late-stage clinical trials of a breast cancer vaccine.